Effects of beetroot juice supplementation on vascular functional and structural changes in aged mice - Masashi Tawa; Keisuke Nakagawa; Mamoru Ohkita (Physiological Reports, 2023)
Abstract This study investigated whether beetroot juice (BRJ) ingestion ameliorates aging‐induced functional and structural changes in vasculature. Aged mice (98–100 weeks old) were supplemented with BRJ (nitrate: 3.5 mmol/L) or drinking water for 4 weeks and compared with young mice (12–15 weeks old). The vasorelaxant response of isolated aortas to acetylcholine was markedly weaker in aged mice than in young mice, but the attenuated relaxation was significantly improved in BRJ‐supplemented aged mice. The acetylcholine‐induced relaxation was completely abolished by Nω‐nitro‐l‐arginine methyl ester in all groups. Additionally, the response to sodium nitroprusside was comparable among the three groups. The aortic medial thickness was significantly greater in aged mice than in young mice, and BRJ supplementation did not suppress this thickening. Plasma nitrate levels were significantly higher in BRJ‐supplemented aged mice than in non‐supplemented aged mice. Conversely, non‐supplemented aged mice had high plasma levels of thiobarbituric acid‐reactive substances, but the levels were suppressed in BRJ‐supplemented aged mice. These findings suggest that BRJ ingestion improves vascular endothelial dysfunction associated with aging, at least in part, by enhancing nitric oxide bioavailability and reducing oxidative stress. Therefore, beetroot ingestion may be a highly useful self‐medication option to prevent vascular aging.